Remainder Theorem


Definition of Remainder Theorem:

Let p(x) be any polynomial of degree greater than or equal to 1 and let α be any real number. If p(x) is divided by the polynomial (x - α), then the remainder is p(α).


In other words:

If the polynomial f(x) is divided by x - α then the remainder R is given by f(x) = (x - α) q(x) + R, where q(x) is the quotient and R is a constant (because the degree of the remainder is less than the degree of the divisor x - α).


Putting x = α, f(α) = (α - α)q(α) + R or f(α) = R

When the polynomial f(x) is divided by x - α, the remainder R = f(α) =  value of f(x) when x is α.



Solved examples on Remainder Theorem:

1. Find the remainder when x\(^{3}\) + 3x\(^{2}\) + 3x +1 is divided by

(i) x + 1

(ii) x - \(\frac{1}{2}\)

(iii) x

(iv) x + γ

(v) 5 + 2x

Solution:

(i) Let f(x) = x\(^{3}\) + 3x\(^{2}\) + 3x +1, divisor is x +1

Then by the Remainder Theorem we get,

Remainder = f(-1)

                  = (-1)\(^{3}\) + 3(-1)\(^{2}\) + 3(-1) +1

                  = -1 + 3 - 3 + 1

                  = 0

(ii) Let f(x) = x\(^{3}\) + 3x\(^{2}\) + 3x +1, divisor is x - \(\frac{1}{2}\)

Then by the Remainder Theorem we get,

Remainder = f(\(\frac{1}{2}\))

                  = (\(\frac{1}{2}\))\(^{3}\) + 3(\(\frac{1}{2}\))\(^{2}\) + 3(\(\frac{1}{2}\)) + 1

                  = \(\frac{1}{8}\) + \(\frac{3}{4}\) + \(\frac{3}{2}\) + 1

                  = \(\frac{1 + 6 + 12 + 8}{8}\)

                  = \(\frac{27}{8}\)

(iii) Let f(x) = x\(^{3}\) + 3x\(^{2}\) + 3x +1, divisor is x i.e., x - 0

Then by the Remainder Theorem we get,

Remainder = f(0)

                  = 0\(^{3}\) + 3 ∙ 0\(^{2}\) + 3 ∙  0 + 1

                  = 1

(iv) Let f(x) = x\(^{3}\) + 3x\(^{2}\) + 3x +1, divisor is x + γ

Then by the Remainder Theorem we get,

Remainder = f(-γ)

                  = (-γ)\(^{3}\) + 3(-γ)\(^{2}\) + 3(-γ) +1

                  = -γ\(^{3}\) + 3γ\(^{2}\) - 3γ +1

(v) Let f(x) = x\(^{3}\) + 3x\(^{2}\) + 3x +1, divisor is 5 + 2x

Then by the Remainder Theorem we get,

Remainder = f(-\(\frac{5}{2}\))

                   = (-\(\frac{5}{2}\))\(^{3}\) + 3(-\(\frac{5}{2}\))\(^{2}\) + 3(-\(\frac{5}{2}\)) + 1

                   = \(\frac{-125}{8}\) + \(\frac{75}{4}\) - \(\frac{15}{2}\) + 1

                   = \(\frac{-125 + 150 -60 + 8}{8}\)

                   = -\(\frac{27}{8}\)



2. If 3x\(^{2}\) - 7x + 11 is divided by x - 2 then find the remainder.

Solution:

Here p(x) = 3x\(^{2}\) - 7x + 11, divisor is x - 2

Therefore, remainder = p(2)                    [Taking x = 2 from x - 2 = 0]

                                   = 3(2)\(^{2}\) - 7(2) + 11

                                   = 12 - 14 + 11

                                   = 9










10th Grade Math

From Remainder Theorem to HOME




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.